2005
DOI: 10.1111/j.1399-0039.2005.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging new alleles suggest high diversity of HLA‐C locus

Abstract: Human leukocyte antigen (HLA)-C has only recently emerged as an important transplantation antigen and as a receptor for natural killer cells. Over the last few years, sequence-based typing (SBT) revealed the true diversity of HLA-C locus; however, the frequency at which new alleles are detected still remains high. During routine SBT of 3500 samples for the National Marrow Donor Program, we have identified 20 new HLA-C alleles reported in this article in 26 individuals. New variants have been characterized by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
1
22
2
Order By: Relevance
“…3500 NMDP donors. The frequency of emerging new alleles still remains high, and some new alleles Cw*030304, 0413 detected four and three times in African Americans, respectively, suggesting that HLA-C common to African Americans and probably other minorities is still not adequately characterized [11]. In this study, we examined 1795 Chinese Han donors by SBT and identified nine novel HLA-C alleles with a new allele emerging rate of 0.5% (9/1795), which is comparable to that reported by Lebedeva et al (0.57%, 20/3500).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…3500 NMDP donors. The frequency of emerging new alleles still remains high, and some new alleles Cw*030304, 0413 detected four and three times in African Americans, respectively, suggesting that HLA-C common to African Americans and probably other minorities is still not adequately characterized [11]. In this study, we examined 1795 Chinese Han donors by SBT and identified nine novel HLA-C alleles with a new allele emerging rate of 0.5% (9/1795), which is comparable to that reported by Lebedeva et al (0.57%, 20/3500).…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, HLA-C typing by SBT was restricted to analyze polymorphisms at exons 2 and 3 [10,11,19,20]. The HLA-C diversity and novel polymorphisms had been reported for NMDP samples of which the majority are of Caucasian origin, but the allelic diversity of HLA-C in non-Caucasians is still underestimated [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HLA-C emerges as an important transplantation antigen and as a receptor for natural killer cells. 28 HLA-C is up-regulated in GBM; therefore its presence could promote tumorigenesis.…”
mentioning
confidence: 99%